Using 3D design technology and a combination of carbon fiber and 16% HGM epoxy resin, female troops are wearing bulletproof vests - Agnes Sprakezia Lubis; Sovian Aritonang; Raditya Faradina; Vishal R Panse (FoundAE, 2024)
Women are becoming more active in the defense industry. Since the morphology of the female body differs from that of the male during military activities, it is required to modify personal protection equipment to accommodate the female body shape. According to a literature review, a survey of a sample of female soldiers from different nations revealed that they felt the impacts of breast soreness when running, as well as a sense of